Analysis of the basic components in technical support programs in Mexico - Villaseñor-Carmona, Víctor H.; Rendón-Medel, Roberto; Martínez-González, Enrique Genaro; Aguilar-Ávila, Jorge (Revista Mexicana de Ciencias Agrícolas, 2026)
In the Mexican agricultural sector, there is a wide diversity of producers, from large and specialized to multi-active and subsistence producers. The latter are related to small production units, which are the subject of attention from government programs aimed at advising them. Nevertheless, the efforts of public technical support programs are characterized by being dispersed and disjointed. This research aimed to analyze the environmental, economic, social, and pedagogical-andragogical contributions of technical support programs in Mexico in the 2019-2023 period through the exploratory analysis of regulatory documents and scientific research on the government programs ‘Production for Wellbeing’ and ‘Sowing Life’, in order to identify points for improvement in future interventions. The results indicated that the agroecological approach within the programs analyzed is partially congruent with the objectives set. The need to develop markets that value sustainability and generate benefits for the program beneficiaries was identified. The component with more options for improvement is the development of indicators to analyze the progress of the proposed objectives.